Cumulative Evidence for Relationships Between Multiple Variants in the TERT and CLPTM1L Region and Risk of Cancer and Non-Cancer Disease - Tian, Jie; Wang, Yan; Dong, Yingxian; Chang, Junke; Wu, Yongming; Chang, Shuai; Che, Guowei (Frontiers in Oncology, 2022)
Background: Genetic studies previously reported that variants in TERT-CLPTM1L genes were related to susceptibility of cancer and non-cancer diseases. However, conclusions were not always concordant. Methods: We performed meta analyses to assess correlations between 23 variants within TERT-CLPTM1L region and susceptibility to 12 cancers and one non-cancer disease based on data in 109 papers (involving 139,510 cases and 208,530 controls). Two approaches (false-positive report probability test, Venice criteria) were adopted for assessing the cumulative evidence of significant associations. Current study evaluated the potential role of these variants based on data in Encyclopedia of DNA Elements (ENCODE) Project. Results: Thirteen variants were stitastically associated with susceptibility to 11 cancers and one non-cancer disease (p<0.05). Besides, 12 variants with eight cancers and one non-cancer disease were rated as strong evidence (rs2736098, rs401681 and rs402710 in bladder cancer, rs2736100, rs2853691 and rs401681 in esophageal cancer, rs10069690 in gastric cancer, rs2736100 and rs2853676 in glioma, rs2242652, rs2736098, rs2736100, rs2853677, rs31489, rs401681, rs402710, rs465498, rs4975616 in lung cancer, rs2736100 in idiopathic pulmonary fibrosis and myeloproliferative neoplasms, rs401681 in pancreatic and skin cancer). According to data from ENCODE and other public databases, 12 variants with strong evidence might fall within putative functional regions. Conclusions: This paper demonstrated that common variants of TERT-CLPTM1L genes were related to susceptibility to bladder, esophageal, gastric, lung, pancreatic and skin cancer, and glioma, myeloproliferative neoplasms, idiopathic pulmonary fibrosis, and besides, the crucial function of the TERT-CLPTM1L region in the genetic predisposition to human diseases is elucidated.